Real Time Water Level Detection Systems for Water Treatment Plant - Mohd Burhanuddin, Hamzah; Nor Azhar, Ahmad (Faculty of Computer Systems & Software Engineering, Universiti Malaysia Pahang, 2016)
“Water Level System” is a system which functioned to detect the water level in a water tank and analyze the data collected. The primary purpose of this software is to improvised current system used by Perbadanan Air Pahang (PAIP). Currently, the method adopts by PAIP required users, to check the system manually. Development of a new system could reduce the management cost with the alert mechanism. This system sends the first SMS when the water tank is nearly full and then the second SMS when the tank is full. It can send least two SMS to the user. The user also can view the record of the reading if they want to analyze the water level pattern. The system also can display the data in graph form to make the data more informative.